MINERALIZATION OF BONE TISSUES AMONG CHILDREN WITH DIFFERENT LEVELS OF PHYSICAL DEVELOPMENT - G.V. Kuznetsova; A.G. Il'in (Педиатрическая фармакология)
The article highlights the data on the physical development of the school aged children, frequency of its violations and age dynamics of indices, characterizing the mineralization of the bone tissue among children. The author confirmed close relations between the mineralization of the bone tissue and the level of the physical development. She showed that some indices of the physical development should be used, while splitting children between the osteopenia and osteoporosis risk groups.Key words: osteopenia among children, physical development, osteoporosis risk groups.